Acute adverse drug reactions following cardiac catheterization: evidence-based guidance for providers and systems - Trooboff, Spencer W.; Iribarne, Alexander (Journal of Thoracic Disease, 2019)
Cardiovascular disease represents a leading source of health loss globally, with an estimated 422 million cases and 18 million deaths attributed to cardiovascular disease in 2015 (1). Diagnostic and therapeutic coronary catheterization (CC) are critical interventions for many of these patients, and over 1 million catheterizations are performed in the United States alone each year (2). CC can generally be performed with low peri-procedural risk. For diagnostic procedures, risk of mortality is less than 0.1% and, when combined with percutaneous coronary intervention, between 0.5% and 2% (3,4). Nevertheless, as with any invasive procedure, there are complications of varying severity associated with CC including contrast-induced nephropathy, cholesterol embolization, local vascular injury, hematoma, pseudoaneurysm, conduction disturbance, stroke and myocardial infarction (5).